2021
DOI: 10.3390/ani11020360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Essential Oils-Based Supplement and Salmonella Infection on Gene Expression, Blood Parameters, Cecal Microbiome, and Egg Production in Laying Hens

Abstract: One of the main roles in poultry resistance to infections caused by Salmonella is attributed to host immunity and intestinal microbiota. We conducted an experiment that involved challenging Lohmann White laying hens with Salmonella Enteritidis (SE), feeding them a diet supplemented with an EOs-based phytobiotic Intebio®. At 1 and 7 days post-inoculation, the expression profiles of eight genes related to immunity, transport of nutrients in the intestine, and metabolism were examined. Cecal microbiome compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 134 publications
(179 reference statements)
0
15
0
1
Order By: Relevance
“…Egg production was increased due to the consumption of rations increased with pandan leaf flour as a source of antioxidants. Feed ingredients contained antioxidants and antibacterial which given to laying hens can improve intestinal performance in the process of absorption of poultry feed nutrients to provide health, and can reduce the death rate of chickens so that egg production can increase (Laptev et al, 2021). Pandan leaf flour level of 4% increases egg production and provides adequate feed conversion.…”
Section: Resultsmentioning
confidence: 99%
“…Egg production was increased due to the consumption of rations increased with pandan leaf flour as a source of antioxidants. Feed ingredients contained antioxidants and antibacterial which given to laying hens can improve intestinal performance in the process of absorption of poultry feed nutrients to provide health, and can reduce the death rate of chickens so that egg production can increase (Laptev et al, 2021). Pandan leaf flour level of 4% increases egg production and provides adequate feed conversion.…”
Section: Resultsmentioning
confidence: 99%
“…The use of plants or derivatives in poultry with Salmonella has had positive effects on performances, whether by reducing mortality (Q. J. Wu et al, 2018), increasing egg production in laying hens (Laptev et al, 2021;Wang et al, 2019) or reducing FCR in broilers (Jazi et al, 2019). The decrease in the FCR can be explained by the increase in the intestinal villi height which have been observed (Jazi et al, 2019; Q. J.…”
Section: Effect Of Plants On Salmonella Colonizationmentioning
confidence: 99%
“…But this can also be explained by the increase in the genus Escherichia-Shigella which has been observed (Gan et al, 2020;Zeng et al, 2018). Some studies have shown that Salmonella Enteritidis was also able to induce an increase in the abundance of other pathogenic/zoonotic bacteria such as Clostridium perfringens or Campylobacter (Laptev et al, 2021; www.efsa.europa.eu/publications EFSA Supporting publication 2024:EN-8597…”
Section: Salmonella Induces Changes In the Evolution Of Gut Microbiot...mentioning
confidence: 99%
“…В качестве источников ФБ изучаются как целые растения, так и выделенные из них активные соединения -апигенин, кверцетин, куркумин и ресвератрол, терпены (эвгенол, тимол, карвакрол, капсаицин и артемизинин) и альдегиды (коричный альдегид и ванилин). Эти молекулы обладают не только противомикробными (в том числе противобактериальными, противогрибным, противовирусными и противопротозойными), но и противовоспалительными, антиоксидантными, иммуномодулирующими свойствами, а также улучшают морфологию и состояние слизистой оболочки кишечника (59)(60)(61).…”
Section: фитобиотики и их действие на таксономический профиль разных ...unclassified